The Effect of Employee Placement on the Job Satisfaction of State Civil Apparatus (ASN) at the Regional Personnel and Human Resources Development Agency (BKPSDM) of Padang City - Raid Dzaki Yurian; Syamsir Syamsir (Darul Yasin Al Sys, 2026)
Employee placement in public institutions has received increasing scholarly attention; however, studies focusing on local personnel agencies remain limited. This study aims to analyze the effect of employee placement on job satisfaction among State Civil Apparatus (ASN) at the Regional Personnel and Human Resources Development Agency of Padang City. A quantitative approach was employed using an associative survey design, involving 30 respondents selected through saturated sampling. Data were collected through questionnaires and interviews and analyzed using descriptive statistics, simple linear regression, t-test, and coefficient of determination with SPSS. The findings indicate that employee placement has a positive and significant effect on ASN job satisfaction, as shown by a t-count of 7.849 and a significance value of 0.000. The R Square value of 0.688 indicates that employee placement explains 68.8% of the variance in job satisfaction, while the remaining 31.2% is influenced by other factors. These findings demonstrate that appropriate employee placement is a crucial factor in improving ASN job satisfaction. Theoretically, this study contributes to public human resource management literature, particularly in relation to person–job fit and merit-based placement. Practically, the findings imply the need to strengthen competency-based placement policies to support more effective, fair, and performance-oriented personnel management in local government institutions.